Implementation of Q&A dialogue system - Výboch, Peter; Vencovský, Filip; Beranová, Lucie; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2021)
Recent neural network architectures, transformers, enabled development of powerful language models pretrained on large sample of language data. Such models can be fine-tuned for downstream tasks. While fine-tuning is not nearly as effortful as training a model from scratch, for complex tasks which require dramatic alterations to the input, it can prove to be effortful. In our work we explore how task of knowledge-base question answering can be cast for a stock RoBERTa transformer pretrained for STS without any fine tuning.
Vedoucí práce: Filip Vencovský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: podniková informatika [obor dipl. práce]; diplomové práce; master's theses